Nomenclatural changes in the grass-feeding Mexican leafhopper genus Cocrassana Blocker & Larsen (Hemiptera: Cicadellidae: Deltocephalinae: Athysanini) - J. Adilson Pinedo-Escatel; C.H. Dietrich; S. McKamey; G. Moya-Raygoza (Revista Brasileira de Entomologia, 2018)
ABSTRACT Two nomenclatural changes are proposed in the tribe Athysanini (Cicadellidae: Deltocephalinae). Chlorotettix sexvarus DeLong, 1959, is newly placed in the genus Cocrassana Blocker & Larsen and is a senior synonym of the type species of Cocrassana, C. riepmai Blocker & Larsen, 1991, syn. nov. A revised diagnosis and illustration of the species are provided.